Pietas ad omnia utilis eſt. M. Mažvydas’s motto - Lemeškin, Ilja (Knygotyra, 2025)
In 1981, the book from the personal library of M. Mažvydas entered scientific circulation. This was indicated by a provenance written in Latin. Next to it, Nojus Feigelman found a Greek text in the same ink colour and similar handwriting, the interpretation of which was difficult. Eventually, these texts became known as the Autograph of M. Mažvydas. The paper examines the genre affiliation of these texts. The conclusion is that both texts represent an extended provenance. Both texts have a distinctive function: one identifies the owner of the book by name, whereas the other text presents his personal motto (symbola, motto). The analysis focuses on how Martynas Mažvydas’s motto functions in Latin and Lithuanian in the 1559 book Forma Chrikſtima.
Keywords: Martynas Mažvydasa; authorship; personal motto; symbola; provenance research